PENGARUH KADAR INTERLEUKIN6 DAN NEURON SPECIFIC ENOLASE TERHADAP LUARAN STROKE ISKEMIK AKUT - Al Rasyid,* Salim Harris,* Muhammad Kurniawan,* Taufik Mesiano,* Rakhmad Hidayat* (NEURONA, 2018)
INTRODUCTION BRAIN BLOOD FLOW DISRUPTION IN ISCHEMIC STROKE WILL TRIGGER CELLS DAMAGE CASCADE AND CAUSED INFARCTION INTERLEUKIN6 IL6 AND NEURON SPECIFIC ENOLASE NSE ARE BRAIN CELLS DAMAGE MARKER THAT CAN BE MARKERS OF ACUTE ISCHEMIC STROKE OUTCOME